2022
DOI: 10.3389/fpls.2022.1062658
|View full text |Cite
|
Sign up to set email alerts
|

Production of active Exendin-4 in Nicotiana benthamiana and its application in treatment of type-2 diabetics

Abstract: GLP-1 (Glucagon-like peptide-1) is a peptide that stimulates insulin secretion from the β-cell for glycemic control of the plasma blood glucose level. Its mimetic exenatide (synthetic Exendin-4) with a longer half-life of approximately 3.3–4 h is widely used in clinical application to treat diabetes. Currently, exenatide is chemically synthesized. In this study, we report that the GLP-1 analogue recombinant Exendin-4 (Exdn-4) can be produced at a high level in Nicotiana benthamiana, with an estimated yield of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated the production of human TGFβ1 in Nicotiana benthamiana, the mature form with biological activity obtained after enterokinase treatment [38]. Based on the specific cleavage property of enterokinase, the fusion protein is released after treatment with this enzyme [39,40]. In this study, to produce bioactive activin A, a cleavage site of enterokinase (D4K) was introduced between the pro-region and mature region of rhAA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the production of human TGFβ1 in Nicotiana benthamiana, the mature form with biological activity obtained after enterokinase treatment [38]. Based on the specific cleavage property of enterokinase, the fusion protein is released after treatment with this enzyme [39,40]. In this study, to produce bioactive activin A, a cleavage site of enterokinase (D4K) was introduced between the pro-region and mature region of rhAA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate that enzyme-resistant GLP-1 analogs could cross the BBB. The half-life of exendin-4 is 2.4-4 h, allowing it to penetrate into the brain after intravenous administration [66,67]. It was found that exendin-4 is soluble in water but exhibits moderate lipophilicity, allowing it to quickly penetrate into the brain after intravenous injection regardless of circumventricular organs which are devoid of the BBB [68].…”
Section: Permeability Of the Blood-brain Barrier Of Glucagon-like Pep...mentioning
confidence: 99%